Decision Support, Knowledge Representation and Management: A Balancing Act between Clinical Use and Implementation of Sophisticated Reasoning Techniques? - Brigl, B.; Managing Editor for the IMIA Yearbook Section on Decision Support, Knowledge Representation and Management (Yearbook of Medical Informatics, 2007)
To position the papers selected for the IMIA Yearbook 2007 in the context of current research in decision support, knowledge representation and management.Synopsis of the articles selected for the IMIA Yearbook 2007.In the Yearbook 2007 the best paper selection of the section Decision support, Knowledge management in Representation’ shows, that the evaluation of the influence of decision support on medical behavior and outcome is as important as research on new reasoning technologies and methods.The best paper selection process shows on the one hand that there is still a deep gap between rather small decision support solutions successfully evaluated in clinical environments and more complex decision support systems using sophisticated reasoning techniques, but lack of clinical use. On the other hand the implementation of decision support systems today benefits from research done in the last decades.
Keywords: Medical informatics; International Medical Informatics Association; yearbook; knowledge management; knowledge representation; decision support; ontologies; temporal data mining; information retrieval